Born for love : reflections on loving - Buscaglia, Leo F. (Thorofare, NJ : SLACK ; [New York] : Distributed by Random House, 1992)
Loving is a choice that offers alternatives to frustration, loneliness and fear ... [we are encouraged] to think, feel and move toward actions that will bring about growth in love. What he suggests is more than a love style--it is a life style
Includes index.
Keywords: Love